Effects of a supplement designed to increase ATP levels on muscle strength, power output, and endurance - Stout Jeffrey R; Ryan Eric D; Herda Trent J; Cramer Joel T (Taylor & Francis Group, 2008)
Abstract Background The present study examined the acute effects of a nutritional supplement intended to improve adenosine triphosphate (ATP) concentrations on vertical jump height, isometric strength of the leg extensors, leg extension endurance, and forearm flexion endurance. Methods Twenty-four healthy men (mean age ± SD = 23 ± 4 yrs, stature = 181 ± 7 cm, and body mass = 82 ± 12 kg) volunteered to complete a familiarization trial plus 2 randomly-ordered experimental trials separated by a 7-day washout period. Participants received either 6 (body mass < 91 kg) or 8 (body mass ≥ 91 kg) tablets of the treatment (TR; 625 mg of adenylpyrophosphoric acid and calcium pyruvate, 350.8 mg of cordyceps sinensis extract and yohimbine hydrochloride) or placebo (PL; 980 mg of microcrystalline cellulose) 1 hour prior to the following tests: countermovement vertical jump (CVJ), forearm flexion repetitions to exhaustion, isometric maximal voluntary contractions (MVCs) of the leg extensors, and a 50-repetition maximal concentric isokinetic leg extension endurance test. Results There were no differences between the TR and PL trials for CVJ height (P > 0.05), isometric MVC peak torque (P > 0.05), maximal concentric isokinetic peak torque (P > 0.05), percent decline during the leg extension endurance tests (P > 0.05), or repetitions to exhaustion during the forearm flexion endurance tests (P > 0.05). Conclusion These findings indicated no improvements in the measured variables as a result of ingesting this nutritional supplement. Future studies should examine whether chronic supplementation or a loading period is necessary to observe any ergogenic effects of this supplement.